Telaah potensi hybrid vigor sifat bobot badan pada silangan kambing Boer dan Jawarandu - Sigit Prastowo; Yayang Resty Nurhayat; Ignatia Fanny Indah Widowati; Tristianto Nugroho; Nuzul Widyas (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
Crossbreeding program was an option in order to improve Indonesian local goat productivity. In general, crossbreeding is aimed to utilize the benefit ofheterosis (hybrid vigor: HV); where better offspring performance compared to its parents phenotype is expected. Currently, crossbreeding between Boer bucks and  Jawarandu does is widely practised; resulting in a crossbred called Boerja. However, information regarding the HV effect were less available. Thus, this study aims to calculate HV in Boer × Jawarandu in relative to the mid-parental average, and relative to the dam phenotype. Mature body weight (BW) of 504 head of goat derived from Boer buck (n=6), Jawarandu doe (n=15), Boerja F1 (n=298), Boerja F2 (n=167), and Boerja F3 (n=18) were analyzed. Backcross system was applied to produce Boerja F2 (Boer ♂ × Boerja F1 ♀)  and Boerja F3 (Boer ♂ × Boerja F2 ♀). Result shows that BW in Boer, Jawarandu, Boerja F1, Boerja F2, and Boerja F3 were 79,00 ± 16,21; 29,07 ± 3,76; 41,84 ± 4,12; 41,69 ± 3,68 and 39,96 ± 4,97 kg respectively. The heterosis value of Boerja F1, Boerja F2, and Boerja F3 in relative to the parents average were -23, -31, and -34%, while in relative to the dam were 44, 0, and -4% respectively. According to HV value, it is concluded that the most optimum result of Boer × Jawarandu crossbreeding was found in Boerja F1. Higher Boer breed proportion in F2 and F3 were found to have lower BW.